Low-velocity impact characteristics of closed cell AA2014-SiCp composite foam. (1st March 2019) - Sahu, S.; Mondal, D.P.; Cho, J.U.; Goel, M.D.; Ansari, M.Z.
Abstract: Deformation behaviour of closed cell aluminium alloy (AA2014) −10 wt % silicon carbide particles (SiCp ) composite foam is studied under static and impact loading conditions. Foam is fabricated through liquid metallurgy route. Static compression tests are performed at an equivalent strain rate of 0.01/s and drop-weight impact tests are performed at an impact velocity of about 0.80 m/s. Based on these tests, Young's modulus, plateau stress, and densification strain of the foam are determined. Finite element analysis is used to simulate the static and impact tests and numerical simulation results are compared with the experimental results for fracture behavior of the foam. Results show the brittle but high strength characteristic of the foam. Further, experimental and simulation results shows good conformity. Based on this study, it is found that a peak load of about 520 N is required to cause the foam fracture and complete perforation under the impact test.